(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Are there any statistically significant differences in the characteristics of the management in emergency activities in cases of increased scope of work depending on location institutions and by sex and age of the team members? Purpose: The purpose of the research was to find out what are the opinions from the members of the emergency team about managerial and communication skills of leaders of emergency teams in crisis situations, which in turn affect the relations within the team. Method: In the research was used non experimental method. The data were collected using a structured questionnaire, on a sample of employed nurses in the emergency units in General Hospital Jesenice (SB Jesenice) (n = 41) and Novo mesto General Hospital (SB Novo mesto) (n = 42). The questionnaire was pre-tested. Selected data were analyzed by t-test. Results: The results of the research showed statistical differences in the context of the following claims: (no) "Head separates the other members of the individuality" (t = 1.118, p = 0.040). Respondents aged up to and including 35 years largely agree with the statement than respondents aged 36 years onwards; (Ii) "Head of us before taking a decision, always well presented« (t = -1.481, p = 0.030), where women are in the majority less agree with the statement; (Iii) "Head of the decision-making using different pressures (mobbing)" (t = -0.373, p = 0.018). Respondents from General hospital Jesenice largely deny this claim as respondents in the General hospital Novo mesto; (Iv) "Head of avoiding conflicts, because it is inconvenient" (t = 2.580, p = 0.013). In the claims (iii) and (iv) Representative of the women expressed greater agreement. Organization: The research results are given managers at all levels of the organization a clear picture of the view of the members of the emergency teams on the characteristics of management in case of increased workload. Society: An organizational culture and method of governance may encourage organizations on the basis of the characteristics of other organizations, bringing in its new environmental management approaches and so improve their relations. Originality: In the case of research the results relating to the two emergency center two Slovenian general hospitals. A similar survey within the emergency teams has not been completed. Limitations/Future Research: The main limitation of the research is in the number of respondents. The reason why is that the survey only took place in the emergency departments of two general hospitals in Slovenia. In Slovenia the final stages of opening regional emergency centers. Since this is a new and separate section of the hospital, in which working processes will be included under the new staff, we believe that it will be necessary to ensure the quality of organization and management team in the future, a similar study (longitudinal) carried out in all ten emergency centers.